(untitled) (Development Service Industry Management, 2025)
The purpose of the article is to identify scientific approaches to marketing management for the strategic management of the development of the market potential of small enterprises in conditions of high volatility and uncertainty of the market. One of the tasks is to reflect the capabilities of innovative digital technologies to increase the market potential of small enterprises and increase their competitiveness. It is argued that marketing management should be considered as a key tool for the development of the market potential of small businesses, which ensures not only the survival of the enterprise in competitive conditions, but also the creation of prerequisites for sustainable growth and expansion of market share. It is emphasized that the concept of marketing management is based on the methodological approach of value-oriented management and involves combining a strategic approach with the operational implementation of specific solutions. This is especially important for small businesses that cannot always distinguish between management levels due to limited staff or resource constraints. The essence of marketing management is outlined, its main advantages in solving management problems. The principles (approaches) of marketing management are highlighted and correlated with the tasks of realizing the market opportunities of small businesses. The types of modern digital technologies that contribute to the realization and development of the market potential of small businesses are characterized and differentiated in terms of strategic and operational marketing. It is emphasized that marketing management contributes to the effectiveness of innovative activities in the business environment. Examples of Ukrainian companies that effectively use the latest innovative technologies for business development and ensuring its competitiveness are given.